Anticolonial and Postcolonial Narratives in the Context of Political Myth in the DPRK and the Republic of Korea - N. N. Kim; A. V. Soloviev (Международная аналитика)
This article delves into the intricate ways in which anti- and postcolonial narratives shape the formation of political myths in both the Democratic People’s Republic of Korea (DPRK) and the Republic of Korea. Political myth, as a discursive system, elucidates how people are molded and what objectives they serve through a complex interplay of signs and symbols. Having established the prerequisites for when historical narrative converges with political myth (drama, signiﬁcance, and political action), the authors identify three clusters of historical narratives, each associated with a signiﬁcant trauma: the loss of independence, the attainment of independence through external aid, and the division of the people. Scrutinizing these narratives, the authors extract common and speciﬁc features of political myths as they manifest in the North and South, and pinpoint the key historical and political circumstances that account for these divergences and convergences.